Catalyst for directly preparing ethanol from synthesis gas and preparation method thereof
By using a catalyst supported by hydroxylated support with active metal oxides and alkali metal additives, the existing catalysts with low activity and complex product distribution are solved, and the effect of efficient synthesis of ethanol at low temperature and low pressure is achieved, and good industrial application is achieved. prospect.
Patent Information
- Application Number
- CN202411395535.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-11
AI Technical Summary
The existing catalysts for directly preparing ethanol in synthesis gas have problems such as low activity, wide distribution of alcohol products, and complex catalyst preparation, which is difficult to meet the needs of industrial production.
The catalyst is prepared by using a hydroxylated support supported active metal oxide and alkali metal additive, and the silicon-aluminum composite oxide is treated by concentrated sulfuric acid/H2O2 solution, and the catalyst is prepared by combining the calcination and impregnation steps.
Ethanol is efficiently synthesized at lower reaction temperatures and pressures. The alcohol products have higher ethanol selectivity and fewer other alcohols, especially the absence of C4+ alcohol, which reduces subsequent separation energy consumption and has good industrial application prospects.
Smart Images

Figure CN119406413A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of synthesis gas conversion, relates to a method for preparing ethanol by utilizing synthesis gas, and in particular to a catalyst for preparing ethanol by directly converting synthesis gas and a preparation method thereof. Background Art
[0002] As an important bulk chemical raw material, high-quality liquid fuel and liquid additive, ethanol is widely used in energy, chemical, medicine, agriculture and other fields.
[0003] Ethanol not only has chemical energy comparable to gasoline, but also has lower sulfur and ash content, and is less harmful to the human body. It is considered one of the best fuels to replace and save gasoline. It can also be added to gasoline in any proportion and is a high-quality liquid fuel. Ethanol is also an important chemical raw material, used to prepare acetaldehyde, ether, ethyl acetate, acetic acid, etc., and derives many intermediates for products such as medicines, dyes, and pesticides. Ethanol can also produce bulk chemicals and fine chemical products such as higher ketones and higher carbon alcohols, which are used as a source of hydrogen in fuel cells. As a chemical platform compound, it has huge room for development.
[0004] Existing ethanol production methods include grain fermentation, ethylene hydration, acetaldehyde hydrogenation, dimethyl ether carbonylation, and direct synthesis gas production. Grain fermentation has the problem of "competing with people for grain"; ethylene hydration requires a large amount of ethylene, an important petrochemical raw material, and is subject to raw material supply constraints; acetaldehyde hydrogenation has a high investment cost; and the indirect method of preparing ethanol from synthesis gas via methanol-dimethyl ether-methyl acetate-ethanol has a long path and high energy consumption.
[0005] Therefore, the one-step method of directly preparing ethanol from syngas is undoubtedly a promising route. However, this process has not yet been applied on a large scale, mainly because the developed catalyst is not suitable for industrial production. The research focus of directly preparing ethanol from syngas is still to develop catalysts with good catalytic performance, low cost and good stability.
[0006] Catalysts for direct synthesis of ethanol from syngas can generally be divided into four categories: precious metal rhodium-based catalyst system (Rh), modified FT catalyst system (Fe, Co, etc.), modified methanol catalyst system (CuZnAl), and molybdenum-based catalyst system (Mo). Among them, although rhodium-based catalysts have high ethanol selectivity and activity, they are limited by the cost of precious metal raw materials; the modified FT catalyst system has more hydrocarbon products, especially methane; the modified methanol catalyst system has the problem of low ethanol selectivity; and although the molybdenum-based catalyst system shows excellent sulfur resistance and reaction activity, it needs to be carried out at higher temperature and pressure.
[0007] CN 103764277A discloses an alkali metal-modified RhMn-based catalyst for synthesizing oxides. However, the synthesis product of the catalyst has complex components, mainly oxygen-containing compounds such as acetic acid, ethanol, methyl formate, and methyl acetate, and the gas phase product is mainly methane.
[0008] CN 111420684A relates to a K-modified molybdenum selenide catalyst, which can be used for heating at 340°C, 10MPa, and 3000h. -1 The CO conversion rate under the condition of H2 / CO=1 was 8.6%, the selectivity of alcohol, hydrocarbon and CO2 were 43.4, 26.3 and 30.3% respectively, and the methanol, ethanol, propanol and C 3+ The mass percentages of alcohol are 23.3, 54.6, 17.3 and 4.9% respectively. Although the selectivity of ethanol is high, the reaction conditions are harsh.
[0009] CN 108325548A reports an alkali metal modified MoS2 catalyst with excellent sulfur resistance, but the product using the catalyst contains a large amount of CO2 and methanol.
[0010] CN 106513001A reports a catalyst for preparing ethanol from synthesis gas, which is composed of CuO, ZrO2, K2O and a carrier. The ethanol selectivity of the catalyst is higher than 40%, but CO2 and hydrocarbon products are still more, both above 15%, and the alcohol product also contains C 5+ Alcohol has a complex composition and is difficult to separate subsequently.
[0011] CN 110280261A discloses a catalyst for directly synthesizing ethanol from synthesis gas, its preparation method and application. The catalyst is composed of Cu, Co, Mg, Mn oxides prepared by a hydrotalcite precursor method and trivalent metal oxides (Al2O3, Fe2O3, Ga2O3, etc.). The ethanol selectivity is higher than 60%, but the CO conversion rate is low. When the ethanol selectivity is the highest (75.2%), the CO conversion rate is only 32.2%, and the alcohol product also contains C 5+ Alcohol, complex composition, high energy consumption for subsequent separation. In addition, the preparation process of the catalyst is complicated, not only requires reflux, but also consumes a large amount of ethanol in the washing process of the precipitate.
[0012] The above studies show that the currently developed catalysts for direct synthesis of ethanol from syngas have the disadvantages of low activity, wide distribution of alcohol products, and complex catalyst preparation, which are not conducive to the industrial production of ethanol. It is of great significance to develop catalysts with high activity, high ethanol selectivity, and a single alcohol product composition. Summary of the invention
[0013] The purpose of the present invention is to overcome the problems existing in the prior art and provide a catalyst for directly converting ethanol from synthesis gas and a preparation method thereof.
[0014] The catalyst for direct synthesis of ethanol from synthesis gas of the present invention is composed of a hydroxylated carrier loaded with active metal oxide and an alkaline metal additive, and its mass percentage composition is: 68-80wt% of the hydroxylated carrier, 19-31wt% of the active metal oxide, and 1-1.8wt% of the alkaline metal additive.
[0015] The hydroxylated carrier is obtained by pre-treating the silicon-aluminum composite oxide by hydroxylation with concentrated sulfuric acid / H2O2 solution and then calcining it.
[0016] Specifically, in the silicon-aluminum composite oxide of the present invention, the mass ratio of SiO2 to Al2O3 is preferably 1:0.5-1.
[0017] More specifically, the silicon-aluminum composite oxide is preferably a mixture of nano-SiO2 and γ-Al2O3, or a mixture of B-type silica gel (B-SiO2) and γ-Al2O3.
[0018] Furthermore, the active metal oxide described in the present invention is one or a mixture of several of copper, cobalt and iron oxides in any proportion.
[0019] Furthermore, the basic metal additive described in the present invention is any one or two of cesium, strontium and calcium oxide.
[0020] Furthermore, the present invention also provides a method for preparing the catalyst for direct synthesis of ethanol from synthesis gas, which specifically comprises:
[0021] S1, pre-treating the silicon-aluminum composite oxide by impregnation with concentrated sulfuric acid / H2O2 solution, and obtaining a hydroxylated carrier by drying and calcining;
[0022] S2, impregnating the hydroxylated support in an aqueous solution of an active metal soluble salt, and obtaining a supported catalyst by drying and calcining;
[0023] S3, mixing the supported catalyst with an aqueous solution of a soluble salt of an alkaline auxiliary agent, and then impregnating, drying and calcining to obtain the catalyst.
[0024] Wherein, the volume ratio of the concentrated sulfuric acid / H2O2 solution is preferably 0.5-2:1.
[0025] Furthermore, the calcination temperatures of the hydroxylated carrier, the carrier catalyst and the catalyst in the present invention are preferably 400-600° C., and the calcination time is preferably 5-10 h.
[0026] In the present invention, the active metal soluble salt in step S2 preferably includes a soluble salt of copper and / or a soluble salt of a Group VIII metal. Furthermore, the soluble salt of a Group VIII metal is preferably an iron salt or a cobalt salt.
[0027] Furthermore, in the aqueous solution of the active metal soluble salt, the total concentration of active metal ions is preferably 1.0 to 3.0 mol / L.
[0028] In the present invention, the alkaline auxiliary agent soluble salt in step S3 preferably includes one or two of soluble cesium salt, strontium salt or calcium salt.
[0029] Furthermore, in the aqueous solution of the alkaline auxiliary agent soluble salt, the total concentration of metal ions is preferably 0.1 to 0.5 mol / L.
[0030] The catalyst prepared by the present invention can be used as a catalyst for preparing ethanol by directly converting synthesis gas, and can be applied to the process of directly preparing ethanol from synthesis gas.
[0031] The present invention provides a catalyst for directly preparing ethanol from synthesis gas. The catalyst comprises a hydroxylation carrier obtained by treating a silicon-aluminum composite oxide with a concentrated sulfuric acid / H2O2 solution, and the carrier is loaded with active metal oxides and alkaline metal additives. The catalyst uses non-precious metals as active components, has a simple catalyst preparation process, and has low production cost.
[0032] The catalyst of the present invention is used for catalyzing the direct production of ethanol from synthesis gas, and can efficiently synthesize ethanol at a relatively low reaction temperature and pressure, with a relatively high selectivity of ethanol in the alcohol product and a relatively low selectivity of other alcohols, especially without C 4+ Alcohol, which reduces the energy consumption of subsequent separation and has better industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is the STEM image of the catalyst prepared by the support before and after hydroxylation. Implementation
[0034] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.
[0035] The production processes, experimental methods or detection methods involved in the embodiments and comparative examples of the present invention are all conventional methods in the prior art unless otherwise specified, and their names and / or abbreviations are all conventional names in the field and are very clear and unambiguous in the relevant application fields. Those skilled in the art can understand the conventional process steps based on the names and apply the corresponding equipment to implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0036] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art.
[0037] The catalyst for directly preparing ethanol from synthesis gas of the present invention comprises a carrier, an active metal oxide and an alkaline metal auxiliary agent loaded on the carrier.
[0038] The carrier is a hydroxylated carrier, which is composed of silicon-aluminum composite oxide after hydroxylation treatment.
[0039] Preferably, the carrier is a mixture of hydroxylated nano-SiO2 and hydroxylated γ-Al2O3, or a mixture of hydroxylated B-SiO2 and hydroxylated γ-Al2O3.
[0040] The specific hydroxylation process is to treat the silicon-aluminum composite oxide with concentrated sulfuric acid / H2O2 solution and then calcine it to obtain it.
[0041] Preferably, the mass ratio of SiO2 to Al2O3 in the silicon-aluminum composite oxide is 1:0.5-1, more preferably 1:0.4-0.9, and even more preferably 1:0.4-0.8.
[0042] The active metal oxide is preferably any two or three of CuO, Fe2O3, and Co2O3, accounting for 19 to 31 wt% of the catalyst mass; the alkaline metal additive is preferably one or two of Cs2O, SrO, and CaO, accounting for 0.9 to 1.8 wt% of the catalyst mass.
[0043] The method for preparing the catalyst for direct synthesis of ethanol from synthesis gas of the present invention specifically comprises the following steps:
[0044] 1) After impregnating the silicon-aluminum composite oxide with a concentrated sulfuric acid / H2O2 solution, drying and calcining to obtain a hydroxylated carrier;
[0045] 2) The hydroxylated support is immersed in an aqueous solution of an active metal soluble salt, and then dried and calcined to obtain a supported catalyst;
[0046] 3) The supported catalyst is mixed with an aqueous solution of a soluble salt of an alkaline auxiliary agent, and then impregnated, dried, and calcined to obtain the catalyst.
[0047] Preferably, in step 1), the volume ratio of the concentrated sulfuric acid / H2O2 solution is preferably 0.5-2:1; the mass volume ratio of the silicon-aluminum composite oxide to the concentrated sulfuric acid / H2O2 solution is preferably 0.1-0.5 g:1 mL, further preferably 0.2-0.4 g:1 mL, and more preferably 0.2-0.3 g:1 mL.
[0048] Preferably, the immersion temperature in step 1) is preferably 30-80°C, more preferably 50-80°C, more preferably 60-70°C; the immersion time is preferably 2-10h, more preferably 3-8h, more preferably 5-6h.
[0049] Preferably, the silicon-aluminum composite oxide after the impregnation treatment in step 1) is washed with water until it becomes neutral, and then dried and calcined in sequence.
[0050] Preferably, the drying temperature in step 1) is preferably 80-120° C., more preferably 95-105° C., and more preferably 98-102° C.; the drying time is preferably 3-6 h, more preferably 4-7 h, and more preferably 5.5-6.5 h.
[0051] Preferably, the calcination temperature in step 1) is preferably 400-600°C, more preferably 450-550°C, and more preferably 480-520°C; the calcination time is preferably 5-10h, more preferably 6-9h, and more preferably 7-8h.
[0052] Preferably, the solute in the aqueous solution of the active metal soluble salt in step 2) preferably includes copper salt and Group VIII metal salt, and the Group VIII metal salt is preferably iron salt or cobalt salt.
[0053] The copper salt is preferably copper nitrate trihydrate or copper acetate monohydrate, the iron salt is preferably iron nitrate nonahydrate or iron acetate, and the cobalt salt is preferably cobalt nitrate hexahydrate or cobalt acetate.
[0054] Preferably, the total concentration of active metal ions in the aqueous solution of the active metal soluble salt is preferably 1.0 to 3.0 mol / L, more preferably 1.2 to 2.8 mol / L, and even more preferably 1.8 to 2.2 mol / L.
[0055] Preferably, when the solutes in the aqueous solution of the active metal soluble salt are iron salt and copper salt, the molar ratio of the iron salt to the copper salt is preferably 0.3-1:1, more preferably 0.2-0.9:1, and more preferably 0.5-0.7:1; when the solutes in the aqueous solution of the active metal soluble salt are cobalt salt and copper salt, the molar ratio of the cobalt salt to the copper salt is preferably 0.3-1.5:1, more preferably 0.4-1.2:1, and more preferably 0.6-0.8:1.
[0056] Preferably, in step 2), the mass volume ratio of the hydroxylated support to the aqueous solution of the active metal soluble salt is preferably 0.2-0.7 g:1 mL, more preferably 0.3-0.6 g:1 mL, and even more preferably 0.4-0.6 g:1 mL.
[0057] Preferably, in step 2), the immersion temperature is preferably 30-70°C, more preferably 40-60°C, and more preferably 50-55°C; the immersion time is preferably 2-6h, more preferably 3-5h, and more preferably 3.5-4.5h.
[0058] Preferably, the hydroxylated carrier after the impregnation treatment in step 2) is subjected to ultrasonic evaporation and drying in sequence, and then calcined.
[0059] Preferably, in step 2), the ultrasonic evaporation frequency is preferably 20 to 100 KHz, more preferably 30 to 80 KHz, and more preferably 40 to 50 KHz; the ultrasonic evaporation time is preferably 5 to 15 h, more preferably 7 to 13 h, and more preferably 10 to 12 h; the drying temperature is preferably 80 to 120° C., more preferably 90 to 100° C., and more preferably 92 to 98° C.; the drying time is preferably 4 to 8 h, more preferably 5 to 7 h, and more preferably 5.5 to 6.5 h.
[0060] Preferably, in step 2), the calcination temperature is preferably 400-600° C., more preferably 450-480° C., more preferably 500-550° C.; the calcination time is preferably 5-10 h, more preferably 6-9 h, more preferably 7-8 h.
[0061] Preferably, the solute in the aqueous solution of the alkaline auxiliary agent soluble salt in step 3) preferably includes one or two of soluble cesium salts, strontium salts or calcium salts.
[0062] The soluble cesium salt is cesium nitrate or cesium chloride; the soluble strontium salt is strontium nitrate or strontium dichloride; and the soluble calcium salt is calcium nitrate or calcium dichloride.
[0063] Preferably, the total concentration of metal ions in the aqueous solution of the alkaline auxiliary agent soluble salt is preferably 0.1 to 0.5 mol / L, more preferably 0.15 to 0.45 mol / L, and even more preferably 0.2 to 0.3 mol / L.
[0064] Preferably, when containing a soluble cesium salt and a strontium salt, the molar ratio of the cesium salt to the strontium salt is preferably 0.7-1.5:1, more preferably 0.5-1.3:1, and more preferably 0.6-0.8:1; when containing a soluble cesium salt and a calcium salt, the molar ratio of the cesium salt to the calcium salt is preferably 0.1-0.3:1, more preferably 0.1-0.2:1, and more preferably 0.13-0.18:1; when containing a soluble strontium salt and a calcium salt, the molar ratio of the strontium salt to the calcium salt is preferably 0.9-1.2:1, more preferably 0.95-1.15:1, and more preferably 0.98-1.12:1.
[0065] Preferably, in step 2), the mass volume ratio of the supported catalyst and the aqueous solution of the soluble salt of the alkaline auxiliary agent is preferably 0.1-0.6 g:1 mL, more preferably 0.2-0.5 g:1 mL, and more preferably 0.3-0.4 g:1 mL.
[0066] Preferably, the immersion temperature in step 3) is preferably 30-80°C, more preferably 40-70°C, and more preferably 50-60°C; the immersion time is preferably 3-7h, more preferably 4-6.5h, and more preferably 5-6h.
[0067] Preferably, the supported catalyst after the impregnation treatment in step 3) is subjected to ultrasonic evaporation and drying in sequence, and then calcined.
[0068] Preferably, in step 3), the ultrasonic evaporation frequency is preferably 20 to 100 KHz, more preferably 30 to 55 KHz, and more preferably 40 to 50 KHz; the ultrasonic evaporation time is preferably 6 to 18 hours, more preferably 8 to 15 hours, and more preferably 10 to 14 hours; the drying temperature is preferably 80 to 120° C., more preferably 95 to 105° C., and more preferably 98 to 102° C.; the drying time is preferably 4 to 8 hours, more preferably 5 to 7 hours, and more preferably 6 to 6.5 hours.
[0069] Preferably, in step 3), the calcination temperature is preferably 400-600°C, more preferably 450-550°C, and more preferably 460-530°C; the calcination time is preferably 5-10 hours, more preferably 5.5-7 hours, and more preferably 6-6.5 hours.
[0070] The catalyst prepared by the present invention can be used as a catalyst for preparing ethanol by directly converting synthesis gas, and can be applied to the process of directly preparing ethanol from synthesis gas.
[0071] Preferably, when the catalyst is used to catalyze the reaction of preparing ethanol from synthesis gas, it is necessary to first reduce the catalyst using reducing gas, and then introduce the synthesis gas to carry out the catalytic reaction.
[0072] The reducing gas is preferably H2 / N2, and the ratio of H2 / N2 in the reducing gas is preferably 10 to 30:100, more preferably 15 to 25:100, and even more preferably 18 to 20:100.
[0073] Preferably, the reducing gas space velocity is 500 to 2000 h -1 , more preferably 800 to 1700 hours -1 , more preferably 1000 to 1500 hours -1The reduction temperature is preferably 250-400°C, more preferably 260-380°C, and more preferably 300-350°C.
[0074] The H2 / CO ratio in the synthesis gas is preferably 1-3:1, more preferably 1.5-2.5:1, and even more preferably 1.8-2.0:1.
[0075] Preferably, the reaction temperature is preferably 220-300°C, more preferably 230-280°C, and more preferably 240-260°C; the reaction pressure is preferably 2.0-5.0MPa, more preferably 2.5-4.5MPa, and more preferably 3-4MPa; the synthesis gas space velocity is preferably 2000-7000h -1 , more preferably 3000 to 6000 hours -1 , more preferably 4000 to 5000 hours -1 . Example
[0076] Example 1
[0077] Weigh 10g of nano-SiO2 and 10g of γ-Al2O3, mix them, place them in 100mL of concentrated sulfuric acid / H2O2 solution (volume ratio = 1:2), soak them at 30℃ for 2h, take them out, wash them with deionized water until neutral, dry them at 80℃ for 3h, and calcine them at 400℃ for 5h to prepare a hydroxylated carrier.
[0078] 0.048 mol of cobalt nitrate hexahydrate and 0.050 mol of copper nitrate trihydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 1 mol / L.
[0079] 20 g of hydroxylated carrier was added to the above metal salt aqueous solution, immersed at 30° C. for 2 h, and then the solvent was evaporated by ultrasonic wave with a frequency of 20 Hz, dried at 80° C. for 4 h, and calcined at 400° C. for 5 h to prepare a supported catalyst.
[0080] Dissolve 0.0048 mol of strontium nitrate in deionized water to prepare an alkaline solution with a metal ion concentration of 0.1 mol / L.
[0081] Weigh 28 g of supported catalyst, add it to the above alkaline solution, soak it at 30°C for 3 h, evaporate the solvent with ultrasound at a frequency of 20 Hz, dry it at 80°C for 6 h, and calcine it at 600°C for 5 h to prepare the catalyst.
[0082] The catalyst prepared in this example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 10:100 was introduced. The temperature was set to 250°C and the air velocity was 500 h -1, pressure is 100kPa, after 1h of reduction, cut in the synthesis gas with H2 / CO (molar ratio) = 1, at 220℃, 2.0MPa, 2000h -1 The catalyst performance was evaluated under the following conditions.
[0083] The results showed that the CO conversion rate (mol%) was 50.1%; the selectivity of hydrocarbon, CO2 and alcohol products Cmol (standing for "carbon mole", that is, the product composition is expressed by the molar percentage of carbon in each product) was 57.6%, 1.6% and 40.8%, respectively; the distribution of methanol, ethanol, propanol and butanol in alcohol products (Cmol) was 42.1%, 53.1%, 3.8% and 1.0%, respectively.
[0084] Example 2
[0085] Weigh 10g B-SiO2 and 8g γ-Al2O3, mix them, place them in 120mL of concentrated sulfuric acid / H2O2 solution (volume ratio = 1:1), soak them at 50℃ for 5h, take them out, wash them with deionized water until neutral, dry them at 100℃ for 5h, and calcine them at 400℃ for 6h to prepare a hydroxylated carrier.
[0086] 0.038 mol of ferric nitrate nonahydrate, 0.024 mol of cobalt acetate and 0.038 mol of cupric acetate monohydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 1.5 mol / L.
[0087] 18 g of hydroxylated carrier was added to the above metal salt aqueous solution, immersed at 40° C. for 4 h, and then the solvent was evaporated by ultrasonic wave at a frequency of 40 Hz, dried at 100° C. for 5 h, and calcined at 500° C. for 10 h to prepare a supported catalyst.
[0088] Dissolve 0.0007 mol of cesium chloride and 0.0054 mol of calcium nitrate in deionized water to prepare an alkaline solution with a total metal ion concentration of 0.1 mol / L.
[0089] Weigh 26 g of supported catalyst, add it to the above alkaline solution, soak it at 40° C. for 4 h, evaporate the solvent with ultrasound at a frequency of 40 Hz, dry it at 100° C. for 5 h, and calcine it at 500° C. for 10 h to prepare the catalyst.
[0090] The catalyst prepared in this example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 20:100 was introduced. The temperature was set to 300°C and the air velocity was 800 h -1 , pressure is 100kPa, after 6h of reduction, cut in the synthesis gas with H2 / CO (molar ratio) = 2, at 250℃, 3.0MPa, 3000h -1 The catalyst performance was evaluated under the following conditions.
[0091] The results showed that the CO conversion rate (mol%) was 54.6%; the selectivity of hydrocarbon, CO2 and alcohol products (Cmol) were 55.7%, 2.0% and 42.3%, respectively; the distribution of methanol, ethanol, propanol and butanol in the alcohol products (Cmol) were 38.6%, 56.4%, 4.2% and 0.8%, respectively.
[0092] Example 3
[0093] Weigh 10g of nano-SiO2 and 6g of γ-Al2O3, mix them, place them in 60mL of concentrated sulfuric acid / H2O2 solution (volume ratio = 2:1), soak them at 70℃ for 7h, take them out, wash them with deionized water until neutral, dry them at 100℃ for 6h, and calcine them at 450℃ for 6h to prepare a hydroxylated carrier.
[0094] 0.013 mol of ferric acetate, 0.012 mol of cobalt nitrate hexahydrate and 0.025 mol of copper nitrate trihydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 2 mol / L.
[0095] 16 g of hydroxylated carrier was added to the above metal salt aqueous solution, immersed at 50° C. for 4 h, and then the solvent was evaporated by ultrasonic wave at a frequency of 50 Hz, dried at 120° C. for 8 h, and calcined at 450° C. for 8 h to prepare a supported catalyst.
[0096] Dissolve 0.0036 mol of calcium chloride in deionized water to prepare an alkaline solution with a metal ion concentration of 0.1 mol / L.
[0097] Weigh 20 g of supported catalyst, add it to the above alkaline solution, soak it at 50° C. for 4 h, evaporate the solvent with ultrasound at a frequency of 50 Hz, dry it at 120° C. for 8 h, and calcine it at 400° C. for 6 h to prepare the catalyst.
[0098] The catalyst prepared in this example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 30:100 was introduced. The temperature was set to 350°C and the air velocity was 1000 h -1 , pressure is 100kPa, after 5h of reduction, cut in the synthesis gas with H2 / CO (molar ratio) = 2.5, at 240℃, 5.0MPa, 3000h -1 The catalyst performance was evaluated under the following conditions.
[0099] The results showed that the CO conversion rate (mol%) was 56.4%; the selectivity of hydrocarbon, CO2 and alcohol products (Cmol) were 51.2%, 1.2% and 47.6%, respectively; the distribution of methanol, ethanol, propanol and butanol in the alcohol products (Cmol) were 35.0%, 57.8%, 5.4% and 1.8%, respectively.
[0100] Example 4
[0101] Weigh 10g of nano-SiO2 and 7g of γ-Al2O3, mix them, place them in 80mL of concentrated sulfuric acid / H2O2 solution (volume ratio = 1:1), soak them at 80℃ for 8h, take them out, wash them with deionized water until neutral, dry them at 110℃ for 6h, and calcine them at 500℃ for 8h to prepare a hydroxylated carrier.
[0102] 0.025 mol of ferric nitrate nonahydrate and 0.050 mol of copper nitrate trihydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 3 mol / L.
[0103] 17 g of hydroxylated carrier was added to the above metal salt aqueous solution, immersed at 60° C. for 3 h, the solvent was evaporated with ultrasound at a frequency of 40 Hz, dried at 100° C. for 6 h, and calcined at 550° C. for 6 h to prepare a supported catalyst.
[0104] Dissolve 0.0019 mol of strontium dichloride and 0.0018 mol of calcium nitrate in deionized water to prepare an alkaline solution with a total metal ion concentration of 0.1 mol / L.
[0105] 23 g of supported catalyst was weighed and added to the alkaline solution. After being immersed at 60° C. for 3 h, the solvent was evaporated by ultrasonic wave at a frequency of 40 Hz, dried at 100° C. for 5 h, and calcined at 550° C. for 5 h to prepare the catalyst.
[0106] The catalyst prepared in this example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 10:100 was introduced. The temperature was set to 280°C and the air velocity was 2000 h -1 , pressure is 100kPa, after 4h of reduction, cut in the synthesis gas with H2 / CO (molar ratio) = 2, at 300℃, 4.0MPa, 5000h -1 The catalyst performance was evaluated under the following conditions.
[0107] The results showed that the CO conversion rate (mol%) was 63.4%; the selectivity of hydrocarbon, CO2 and alcohol products (Cmol) were 46.6%, 0.8% and 52.6%, respectively; the distribution of methanol, ethanol, propanol and butanol in the alcohol products (Cmol) were 35.9%, 60.2%, 3.2% and 0.7%, respectively.
[0108] Example 5
[0109] Weigh 10g B-SiO2 and 5g γ-Al2O3, mix them, place them in 90mL of concentrated sulfuric acid / H2O2 solution (volume ratio = 2:1), soak them at 40℃ for 10h, take them out, wash them with deionized water until neutral, dry them at 120℃ for 6h, and calcine them at 450℃ for 6h to prepare a hydroxylated carrier.
[0110] 0.036 mol of ferric acetate and 0.038 mol of cupric acetate monohydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 2 mol / L.
[0111] 15 g of hydroxylated carrier was added to the above metal salt aqueous solution, immersed at 70° C. for 6 h, the solvent was evaporated by ultrasonic wave at a frequency of 40 Hz, dried at 140° C. for 5 h, and calcined at 600° C. for 6 h to prepare a supported catalyst.
[0112] Dissolve 0.0014 mol of cesium nitrate and 0.001 mol of strontium nitrate in deionized water to prepare an alkaline solution with a total metal ion concentration of 0.3 mol / L.
[0113] 21 g of supported catalyst was weighed and added to the alkaline solution. After being immersed at 70° C. for 6 h, the solvent was evaporated by ultrasonic wave at a frequency of 40 Hz, dried at 110° C. for 4 h, and calcined at 600° C. for 5 h to prepare the catalyst.
[0114] The catalyst prepared in this example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 10:100 was introduced. The temperature was set to 400°C and the air velocity was 1000 h -1 , pressure is 100kPa, after 4h of reduction, cut in the synthesis gas with H2 / CO (molar ratio) = 1, at 260℃, 3.0MPa, 7000h -1 The catalyst performance was evaluated under the following conditions.
[0115] The results showed that the CO conversion rate (mol%) was 52.9%; the selectivity of hydrocarbons, CO2 and alcohol products (Cmol) were 43.6%, 1.0% and 55.4%, respectively; the distribution of methanol, ethanol, propanol and butanol in the alcohol products (Cmol) were 41.6%, 50.2%, 6.0% and 2.2%, respectively.
[0116] Example 6
[0117] Weigh 10g B-SiO2 and 8g γ-Al2O3, mix them, place them in 150mL of concentrated sulfuric acid / H2O2 solution (volume ratio = 2:2), soak them at 60℃ for 5h, take them out, wash them with deionized water until neutral, dry them at 110℃ for 5h, and calcine them at 500℃ for 10h to prepare a hydroxylated carrier.
[0118] 0.042 mol of cobalt nitrate hexahydrate and 0.031 mol of copper nitrate trihydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 1.8 mol / L.
[0119] 18 g of hydroxylated carrier was added to the above metal salt aqueous solution, immersed at 50° C. for 5 h, and then the solvent was evaporated by ultrasonic wave at a frequency of 30 Hz, dried at 90° C. for 5 h, and calcined at 500° C. for 7 h to prepare a supported catalyst.
[0120] Dissolve 0.0011 mol of cesium nitrate and 0.0045 mol of calcium nitrate in deionized water to prepare an alkaline solution with a total metal ion concentration of 0.2 mol / L.
[0121] Weigh 24 g of supported catalyst, add it to the above alkaline solution, soak it at 50° C. for 5 h, evaporate the solvent with ultrasound at a frequency of 30 Hz, dry it at 90° C. for 5 h, and calcine it at 500° C. for 9 h to prepare the catalyst.
[0122] The catalyst prepared in this example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 20:100 was introduced. The temperature was set to 350°C and the air velocity was 800 h -1 , pressure was 100 kPa, after 4 h of reduction, the synthesis gas with H2 / CO (molar ratio) = 2.5 was introduced, at 270 ° C, 3.0 MPa, 3000 h -1 The catalyst performance was evaluated under the following conditions.
[0123] The results showed that the CO conversion rate (mol%) was 55.9%; the selectivity of hydrocarbon, CO2 and alcohol products (Cmol) were 47.9%, 1.9% and 50.2%, respectively; the distribution of methanol, ethanol, propanol and butanol in the alcohol products (Cmol) were 45.2%, 51.3%, 2.9% and 0.6%, respectively.
[0124] Example 7
[0125] Weigh 10g of nano-SiO2 and 10g of γ-Al2O3, mix them, place them in 100mL of concentrated sulfuric acid / H2O2 solution (volume ratio = 1:2), soak them at 70℃ for 5h, take them out, wash them with deionized water until neutral, dry them at 100℃ for 4h, and calcine them at 400℃ for 6h to prepare a hydroxylated carrier.
[0126] 0.035 mol of ferric nitrate nonahydrate and 0.038 mol of copper nitrate trihydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 1.2 mol / L.
[0127] 20 g of hydroxylated carrier was added to the above metal salt aqueous solution, immersed at 40° C. for 4 h, and then the solvent was evaporated by ultrasonic wave at a frequency of 100 Hz, dried at 100° C. for 6 h, and calcined at 500° C. for 6 h to prepare a supported catalyst.
[0128] Dissolve 0.0021 mol of cesium chloride in deionized water to prepare an alkaline solution with a metal ion concentration of 0.5 mol / L.
[0129] 25.8 g of supported catalyst was weighed and added to the above alkaline solution. After being immersed at 40° C. for 4 h, the solvent was evaporated by ultrasonic wave at a frequency of 100 Hz, dried at 100° C. for 4 h, and calcined at 450° C. for 9 h to prepare the catalyst.
[0130] The catalyst prepared in this example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 20:100 was introduced. The temperature was set to 260°C and the air velocity was 600 h -1 , pressure was 100 kPa, after 6 h of reduction, the synthesis gas with H2 / CO (molar ratio) = 2.5 was introduced, at 220 ° C, 3.0 MPa, 3000 h -1 The catalyst performance was evaluated under the following conditions.
[0131] The results showed that the CO conversion rate (mol%) was 51.2%; the selectivity of hydrocarbon, CO2 and alcohol products (Cmol) were 50.0%, 1.3% and 48.7%, respectively; the distribution of methanol, ethanol, propanol and butanol in the alcohol products (Cmol) were 35.4%, 55.4%, 6.8% and 2.4%, respectively.
[0132] Example 8
[0133] Weigh 10g B-SiO2 and 10g γ-Al2O3, mix them, place them in 90mL of concentrated sulfuric acid / H2O2 solution (volume ratio = 1:1), soak them at 80℃ for 4h, take them out, wash them with deionized water until neutral, dry them at 100℃ for 5h, and calcine them at 450℃ for 8h to prepare a hydroxylated carrier.
[0134] 0.015 mol of ferric acetate, 0.034 mol of cobalt acetate and 0.048 mol of cupric acetate monohydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 2.5 mol / L.
[0135] 20 g of hydroxylated carrier was added to the above metal salt aqueous solution, immersed at 50° C. for 5 h, and then the solvent was evaporated by ultrasonic wave at a frequency of 100 Hz, dried at 110° C. for 8 h, and calcined at 450° C. for 9 h to prepare a supported catalyst.
[0136] Dissolve 0.0071 mol of calcium dichloride in deionized water to prepare an alkaline solution with a metal ion concentration of 0.3 mol / L.
[0137] 27.8 g of supported catalyst was weighed and added to the alkaline solution. After being immersed at 50° C. for 5 h, the solvent was evaporated by ultrasonic wave at a frequency of 100 Hz, dried at 110° C. for 4 h, and calcined at 450° C. for 5 h to prepare the catalyst.
[0138] The catalyst prepared in this example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 10:100 was introduced. The temperature was set to 350°C and the air velocity was 800 h -1 , pressure was 100 kPa, after 3 h of reduction, the synthesis gas with H2 / CO (molar ratio) = 2.5 was introduced, at 260 ° C, 4.0 MPa, 6000 h -1 The catalyst performance was evaluated under the following conditions.
[0139] The results showed that the CO conversion rate (mol%) was 54.2%; the selectivity of hydrocarbon, CO2 and alcohol products (Cmol) were 54.1%, 0.6% and 45.3%, respectively; the distribution of methanol, ethanol, propanol and butanol in the alcohol products (Cmol) were 39.5%, 54.9%, 4.0% and 1.6%, respectively.
[0140] Example 9
[0141] Weigh 10g of nano-SiO2 and 6g of γ-Al2O3, mix them, place them in 160mL of concentrated sulfuric acid / H2O2 solution (volume ratio = 2:1), soak them at 60℃ for 3h, take them out, wash them with deionized water until neutral, dry them at 110℃ for 5h, and calcine them at 500℃ for 4h to prepare a hydroxylated carrier.
[0142] 0.016 mol of ferric nitrate nonahydrate, 0.012 mol of cobalt nitrate hexahydrate and 0.033 mol of copper nitrate trihydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 2.4 mol / L.
[0143] 16 g of hydroxylated carrier was added to the above metal salt aqueous solution, immersed at 70° C. for 6 h, the solvent was evaporated by ultrasonic wave at a frequency of 80 Hz, dried at 110° C. for 8 h, and calcined at 600° C. for 5 h to prepare a supported catalyst.
[0144] Dissolve 0.0011 mol of cesium nitrate and 0.0015 mol of strontium nitrate in deionized water to prepare an alkaline solution with a metal ion concentration of 0.2 mol / L.
[0145] Weigh 20 g of supported catalyst, add it to the above alkaline solution, soak it at 70° C. for 7 h, evaporate the solvent with ultrasound at a frequency of 20 Hz, dry it at 120° C. for 6 h, and calcine it at 600° C. for 3 h to prepare the catalyst.
[0146] The catalyst prepared in this example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 10:100 was introduced. The temperature was set to 360°C and the air velocity was 500 h -1 , pressure is 100kPa, after 5h of reduction, cut in the synthesis gas with H2 / CO (molar ratio) = 2, at 240℃, 5.0MPa, 4000h-1 The catalyst performance was evaluated under the following conditions.
[0147] The results showed that the CO conversion rate (mol%) was 53.8%; the selectivity of hydrocarbon, CO2 and alcohol products (Cmol) were 47.3%, 1.1% and 51.6%, respectively; the distribution of methanol, ethanol, propanol and butanol in the alcohol products (Cmol) were 40.1%, 50.2%, 7.1% and 2.6%, respectively.
[0148] Example 10
[0149] Weigh 10g B-SiO2 and 8g γ-Al2O3, mix them, place them in 70mL of concentrated sulfuric acid / H2O2 solution (volume ratio = 1:1), soak them at 50℃ for 8h, take them out, wash them with deionized water until neutral, dry them at 100℃ for 5h, and calcine them at 600℃ for 5h to prepare a hydroxylated carrier.
[0150] 0.010 mol of ferric nitrate nonahydrate, 0.021 mol of cobalt nitrate hexahydrate and 0.021 mol of copper nitrate trihydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 3 mol / L.
[0151] 18 g of hydroxylated carrier was added to the above metal salt aqueous solution, immersed at 60° C. for 2 h, the solvent was evaporated by ultrasonic wave at a frequency of 70 Hz, dried at 120° C. for 5 h, and calcined at 400° C. for 8 h to prepare a supported catalyst.
[0152] Dissolve 0.0019 mol of strontium dichloride and 0.0021 mol of calcium nitrate in deionized water to prepare an alkaline solution with a total metal ion concentration of 0.1 mol / L.
[0153] Weigh 24 g of supported catalyst, add it to the above alkaline solution, soak it at 40° C. for 3 h, evaporate the solvent with ultrasound at a frequency of 50 Hz, dry it at 110° C. for 6 h, and calcine it at 500° C. for 5 h to prepare the catalyst.
[0154] The catalyst prepared in this example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 20:100 was introduced. The temperature was set to 280°C and the air velocity was 500 h -1 , pressure is 100kPa, after 4h of reduction, cut in the synthesis gas with H2 / CO (molar ratio) = 2, at 280℃, 4.0MPa, 5000h -1 The catalyst performance was evaluated under the following conditions.
[0155] The results showed that the CO conversion rate (mol%) was 58.3%; the selectivity of hydrocarbon, CO2 and alcohol products (Cmol) were 41.6%, 1.4% and 57.0%, respectively; the distribution of methanol, ethanol, propanol and butanol in the alcohol products (Cmol) were 31.9%, 58.7%, 6.9% and 2.5%, respectively.
[0156] Comparative Example 1
[0157] Weigh 10 g of nano-SiO2 and 7 g of γ-Al2O3, mix them, wash them with deionized water until they are neutral, dry them at 110°C for 6 h, and calcine them at 500°C for 8 h to prepare an unhydroxylated carrier.
[0158] 0.025 mol of ferric nitrate nonahydrate and 0.050 mol of copper nitrate trihydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 3 mol / L.
[0159] 17 g of unhydroxylated carrier was added to the above metal salt aqueous solution, immersed at 60° C. for 3 h, and then the solvent was evaporated by ultrasonic wave at a frequency of 40 Hz, dried at 100° C. for 6 h, and calcined at 550° C. for 6 h to prepare a supported catalyst.
[0160] Dissolve 0.0019 mol of strontium dichloride and 0.0018 mol of calcium nitrate in deionized water to prepare an alkaline solution with a total metal ion concentration of 0.1 mol / L.
[0161] 23 g of supported catalyst was weighed and added to the alkaline solution. After being immersed at 60° C. for 3 h, the solvent was evaporated by ultrasonic wave at a frequency of 40 Hz, dried at 100° C. for 5 h, and calcined at 550° C. for 5 h to prepare the catalyst.
[0162] The catalyst prepared in this comparative example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 10:100 was introduced. The temperature was set to 280°C and the space velocity was 2000 h -1 , pressure is 100kPa, after 4h of reduction, cut in the synthesis gas with H2 / CO (molar ratio) = 2, at 300℃, 4.0MPa, 5000h -1 The catalyst performance was evaluated under the following conditions.
[0163] The results showed that the CO conversion rate (mol%) was 35.2%; the selectivity of hydrocarbons, CO2 and alcohol products (Cmol) was 58.2%, 11.5% and 30.3%, respectively; the selectivity of methanol, ethanol, propanol, butanol and C in the alcohol products was 1.3%. 4+ The distribution of alcohols (Cmol) were 60.5%, 32.7%, 4.1%, 1.8% and 0.9%, respectively.
[0164] Figure 1The STEM images of catalysts prepared by loading active metal oxides and alkaline metal additives on different carriers are given. The left and right images are unhydroxylated carriers and hydroxylated carriers, respectively. The white irregular particles in the images are active components. It can be seen from the images that the particle sizes of active components on different carriers are significantly different. The particle size of active components on the catalyst obtained after the carrier is hydroxylated is significantly reduced, which not only promotes the dispersion of active components, but also facilitates the synergistic effect between active components and improves the performance of the catalyst.
[0165] Comparative Example 2
[0166] Weigh 10g of nano-SiO2 and 7g of γ-Al2O3, mix them, place them in 80mL of concentrated sulfuric acid / H2O2 solution (volume ratio = 1:1), soak them at 80℃ for 8h, take them out, wash them with deionized water until neutral, dry them at 110℃ for 6h, and calcine them at 500℃ for 8h to prepare a hydroxylated carrier.
[0167] 0.025 mol of ferric nitrate nonahydrate and 0.050 mol of copper nitrate trihydrate were mixed and dissolved in deionized water to prepare a metal salt aqueous solution with a total metal ion concentration of 3 mol / L.
[0168] 17 g of hydroxylated carrier was added to the above metal salt aqueous solution, and the solution was immersed at 60° C. for 3 h, and then the solvent was evaporated by ultrasonic wave at a frequency of 40 Hz, dried at 100° C. for 6 h, and calcined at 550° C. for 6 h to prepare a catalyst.
[0169] The catalyst prepared in this comparative example was loaded into a fixed bed reactor, and a reducing gas with a volume ratio of H2 to N2 = 10:100 was introduced. The temperature was set to 280°C and the space velocity was 2000 h -1 , pressure is 100kPa, after 4h of reduction, cut in the synthesis gas with H2 / CO (molar ratio) = 2, at 300℃, 4.0MPa, 5000h -1 The catalyst performance was evaluated under the following conditions.
[0170] The results showed that the CO conversion rate (mol%) was 48.4%; the selectivity of hydrocarbons, CO2 and alcohol products (Cmol) was 66.5%, 2.1% and 31.4% respectively; the selectivity of methanol, ethanol, propanol, butanol and C in alcohol products was 1.3%. 4+ The distribution of alcohols (Cmol) were 61.5%, 31.5%, 3.7%, 2.1% and 1.2%, respectively.
[0171] It can be seen from the above 10 embodiments and 2 control examples that the catalyst preparation method of the present invention is simple and low-cost. When used in the direct catalytic preparation of ethanol from synthesis gas, the CO conversion rate is greater than 50% at a relatively low reaction temperature, and the ethanol selectivity in the product is relatively high, both reaching more than 50%, and the highest can reach 60.2%; however, in the control example, not only the CO conversion rate is less than 50%, but the ethanol selectivity in the product is also only about 30%.
[0172] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. A catalyst for direct synthesis of ethanol from synthesis gas, characterized in that The invention relates to a 68-80wt% hydroxylated carrier loaded with 19-31wt% active metal oxide and 0.9-1.8wt% alkaline metal additive, wherein the hydroxylated carrier is obtained by calcining a silicon-aluminum composite oxide after hydroxylation pretreatment with concentrated sulfuric acid / H2O2 solution; the active metal oxide is a mixture of one or more of copper, cobalt and iron oxides in any proportion; and the alkaline metal additive is any one or two of cesium, strontium and calcium oxides.
2. The catalyst for direct synthesis of ethanol from synthesis gas according to claim 1, characterized in that In the silicon-aluminum composite oxide, the mass ratio of SiO2 to Al2O3 is 1:0.5-1.
3. The catalyst for direct synthesis of ethanol from synthesis gas according to claim 1, characterized in that The silicon-aluminum composite oxide is a mixture of nano-SiO2 and γ-Al2O3, or a mixture of B-SiO2 and γ-Al2O3.
4. The method for preparing the catalyst for direct synthesis of ethanol from synthesis gas according to claim 1, characterized in that include: S1, pre-treating the silicon-aluminum composite oxide by impregnation with concentrated sulfuric acid / H2O2 solution, and obtaining a hydroxylated carrier by drying and calcining; S2, impregnating the hydroxylated support in an aqueous solution of an active metal soluble salt, and obtaining a supported catalyst by drying and calcining; S3, mixing the supported catalyst with an aqueous solution of a soluble salt of an alkaline auxiliary agent, and then impregnating, drying and calcining to obtain the catalyst.
5. The method for preparing a catalyst for direct synthesis of ethanol from synthesis gas according to claim 4, characterized in that The volume ratio of the concentrated sulfuric acid / H2O2 solution is 0.5-2:
1.
6. The method for preparing a catalyst for direct synthesis of ethanol from synthesis gas according to claim 4, characterized in that The calcination temperature of the hydroxylation carrier, the carrier catalyst and the catalyst is 400-600° C., and the calcination time is 5-10 hours.
7. The method for preparing a catalyst for direct synthesis of ethanol from synthesis gas according to claim 4, characterized in that The total concentration of active metal ions in the aqueous solution of the active metal soluble salt is 1.0 to 3.0 mol / L.
8. The method for preparing a catalyst for direct synthesis of ethanol from synthesis gas according to claim 4, characterized in that The alkaline auxiliary agent soluble salt includes one or two of soluble cesium salt, strontium salt or calcium salt.
9. The method for preparing a catalyst for direct synthesis of ethanol from synthesis gas according to claim 4, characterized in that The total concentration of metal ions in the aqueous solution of the alkaline auxiliary agent soluble salt is 0.1-0.5 mol / L.
10. Use of the catalyst according to claim 1 as a catalyst for direct conversion of synthesis gas to produce ethanol.
Citation Information
Patent Citations
Catalyst for oxygenate synthesis and method for manufacturing same, device for manufacturing oxygenate, and method for manufacturing oxygenate
CN103764277A
Catalyst for synthesis of ethanol from synthetic gas, preparation method and application thereof
CN106513001A
Molybdenum sulfide-based catalyst for preparing low-carbon alcohol from synthesis gas and preparation method thereof
CN108325548A
Catalyst for directly synthesizing ethanol from syngas and preparation method and application thereof
CN110280261A
Catalyst for directly preparing ethanol from synthesis gas and application
CN111420684A